Single phase matrix converter for inverter operation controlled using Peripheral Interface Controller (PIC): article / Ahmad Hisyam Mansor - Mansor, Ahmad Hisyam (Universiti Teknologi MARA (UiTM), 2010)
This paper is concerned on PIC implementation of design for control the Single Phase Matrix Converter (SPMC) operates as inverter. The SPWM technique was used to synthesize the output. Safe commutation strategy was implemented to avoid voltage spikes due to inductive load. The Insulated Gate Bipolar Transistor act as a power switching devices in the SPMC implementation.